2007
DOI: 10.1111/j.1574-6968.2007.00651.x
|View full text |Cite
|
Sign up to set email alerts
|

Genotype variation and capsular serotypes ofPorphyromonas gingivalisfrom chronic periodontitis and periodontal abscesses

Abstract: Porphyromonas gingivalis is considered an important pathogen in periodontal disease. While this organism expresses a number of virulence factors, no study combining different virulence polymorphisms has, so far, been conducted. The occurrence of combined virulence (Cv) genotypes in 62 isolates of P. gingivalis was investigated from subjects displaying either chronic periodontitis or periodontal abscess. The Cv genotypes, based on gene variation of fimbriae (fimA), Lys-specific cystein proteinase (kgp) and Arg-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0
10

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 31 publications
4
32
0
10
Order By: Relevance
“…Por otra parte, Yoshino y cols. (21) , evaluaron en 62 aislados de P. gingivalis la variabilidad en genes que codifican para factores de virulencia (fimA, kgp y rgpA) y sus serotipos capsulares. En relación a los genotipos descritos para el gen rgpA, estos autores encontraron una prevalencia del 75.8% patrón electroforético A, un 21% presentó el patrón B y un 3.2% correspondió al patrón C (21) .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Por otra parte, Yoshino y cols. (21) , evaluaron en 62 aislados de P. gingivalis la variabilidad en genes que codifican para factores de virulencia (fimA, kgp y rgpA) y sus serotipos capsulares. En relación a los genotipos descritos para el gen rgpA, estos autores encontraron una prevalencia del 75.8% patrón electroforético A, un 21% presentó el patrón B y un 3.2% correspondió al patrón C (21) .…”
Section: Discussionunclassified
“…A la fecha, sólo un estudio ha explorado la prevalencia de ambos genotipos (rgpA y kgp) (21) , por cuanto el objetivo de este trabajo fue describir la frecuencia de los genotipos identificados para los genes rgpA y kgp en aislados clínicos de P. gingivalis provenientes de sujetos chilenos con periodontitis.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…They found that the most prevalent P. gingivalis FimA was type II, which is consistent with previous studies. 77 They observed that Prevotella species were widely present in both healthy and disease samples. Although some species, such as P. nigrescens (ATCC 33563), P. sp.…”
Section: Metagenomics Provides Insight Of Bacterial Profilesmentioning
confidence: 99%
“…Chronic periodontitis is not associated with a particularly virulent clonal type [145]. ATCC 33277 is one of the most commonly employed strains in periodontal research.…”
Section: P Gingivalis Strainsmentioning
confidence: 99%